Dreaming of being chased reflects waking-life experiences related to negative relationships with others metaphorically - Wang, Jiaxi; Feng, Xiaoling (Frontiers in Psychology, 2024)
Introduction It has long been argued that there are dream metaphors which express waking-life experiences indirectly. Most of empirical evidence concerning this topic was in a qualitative way, while few studies explored the topic in a quantitative way. Under this background, we investigated whether dreaming of the typical theme ‘being chased or pursued’ was a metaphorical expression for waking-life experiences related to ‘negative relationships with others’. Methods One hundred and sixty participants reported their waking-life experiences and dreams for a single day. Following this, two external judges rated whether there were any elements related to ‘negative relationships with others’ in both waking-life experiences and dreams. In addition, the judges assessed if there was any content related to ‘being chased or pursued’ in both waking-life experiences and dreams. Results The frequency of dreaming of ‘negative relationships with others’ was higher than the frequency of the same topic in waking-life experiences, which in turn was higher than the frequency of typical theme dreaming of ‘being chased or pursued’. In addition, ‘negative relationships with others’ in waking-life experiences were correlated with both dreaming of ‘being chased or pursued’, and ‘negative relationships with others’ in dreams. Conclusion These results suggested that the typical theme ‘being chased or pursued’ in dreams may represent some waking-life experiences metaphorically. In addition, the results support the threat simulation theory of dreaming, which suggests that threatening events in waking life increase the possibility of threatening events in dreams.